2022
DOI: 10.1021/acs.jmedchem.2c00061
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Isopeptide Bond Formation: A Powerful Tool for the Generation of Potent and Nontoxic Antimicrobial Peptides

Abstract: Antimicrobial peptides (AMPs) have the potential to treat multidrug-resistant bacterial infections. However, the clinical application of AMPs is prevented by their toxicity and poor proteolytic stability. Here, a site-specific approach is used to generate new AMPs to improve their efficacy against bacterial pathogens while reducing their toxicity. We modified and generated a new series of antimicrobial peptides from the leucine- and lysine-rich antimicrobial peptide Amp1L (LKLLKKLLKKLLKLL) by the site-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In contrast, 1018KI11 showed no significant change in MIC values and was superior to nisin, a commonly used food additive that retains only 50% of its initial activity after treatment with papain . All these results indicated that the different positions of lysine isopeptide bonds may lead to different structures of AMPs, which may have an effect on their papain stability . In contrast, bromelain did not show any negative effect on the biological activity of 1018K2–1018KI11 against E.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, 1018KI11 showed no significant change in MIC values and was superior to nisin, a commonly used food additive that retains only 50% of its initial activity after treatment with papain . All these results indicated that the different positions of lysine isopeptide bonds may lead to different structures of AMPs, which may have an effect on their papain stability . In contrast, bromelain did not show any negative effect on the biological activity of 1018K2–1018KI11 against E.…”
Section: Resultsmentioning
confidence: 90%
“…Then, IDR-1018KI2, IDR-1018KI8, and IDR-1018KI11 were designed by forming an isopeptide bond (the positions involved in isopeptide bond formation are K2, K8, and K11) to improve the stability of the AMP. 16 All peptides were synthesized via solid-phase synthesis.…”
Section: Preparation Of Peptidesmentioning
confidence: 99%
“…Another ingenious chemical modification is the introduction of the site-specific isopeptide bond switch in K6L9. One such peptide, Amp1EP9 [ 279 ], is a stable and non-toxic antimicrobial peptide with other possible beneficial functions, such as anticancer and cell-penetrating. Unfortunately, the servers used in this review work only for the proteinogenic amino acids interconnected with peptide bonds.…”
Section: Design Of Cell-penetrating Multifunctional Peptidesmentioning
confidence: 99%
“…Membrane disruptive antimicrobial peptides (AMPs), which occur naturally as part of the innate immune system, offer an opportunity to address multidrug-resistant (MDR) bacteria because of their unspecific mechanism of action, against which resistance does not occur easily. Such AMPs are however unstable in serum and most often toxic owing to their membrane disruptive amphiphilic and usually α-helical structure triggering their antibacterial effect. Their properties can be improved by sequence optimization, whereby the most versatile approach consists in introducing non-natural structural elements such as d -amino acids, non-natural residues, β- or γ-amino acids, , isopeptide bonds, or entirely non-peptidic elements such as spermine or fatty acids. , A complete redesign of AMPs is also possible in the form of dimers, cyclic or bicyclic staples, small molecules, peptoids, , foldamers, or dendrimers. , …”
Section: Introductionmentioning
confidence: 99%